Pemetaan Geologi Desa Kopi, Kecamatan Bulango Utara, Kabupaten Bone Bolango, Gorontalo - Mirdayanti Dachi; Noviar Akase; Sri Maryati (Universitas Negeri Gorontalo, 2026)
Detailed geological information regarding the geomorphology, lithology, and geological structures of Kopi Village, North Bulango District, Bone Bolango Regency, remains limited, despite its importance for geological research, natural resource management, and regional development planning. This study aims to characterize the geomorphological, lithological, and structural features of the area through detailed geological mapping at a scale of 1:10,000. The research employed literature review, field geological surveys, geomorphological observations, outcrop investigations, structural measurements, rock sampling, and megascopic and petrographic analyses. The results reveal four lithological units, namely the Andesite Unit, Diorite Unit, Granodiorite Unit, and Alluvial Unit. Geomorphological analysis identified three landform units consisting of Volcanic Hills, Intrusive Hills, and Alluvial Plains. The geological structures are dominated by tension joints with principal orientations of northwest–southeast (NW–SE) and northeast–southwest (NE–SW). Stratigraphic relationships and petrographic characteristics indicate that andesite represents the oldest unit, subsequently intruded by diorite and granodiorite during the Middle Miocene, whereas alluvial deposits constitute the youngest unit formed by surface sedimentation processes. The geological evolution of the study area is interpreted to have been controlled by magmatic and tectonic activities that influenced the development of lithology, geomorphology, and geological structures. The findings provide detailed geological baseline information that can support future geological investigations and geology-based regional management.